The effects of plyometric training and ß-alanine supplementation on anaerobic power and serum level of carnosine in handball players - Shbib, S.; Rashidlamir, A.; Hakak Dokht, E. (Sport Sciences for Health, 2021)
Background and purpose Plyometric training and ß-alanine supplementation are common among athletes, although its mixed-use had never been investigated in handball players. Thus, a randomized, double-blind, placebo-controlled trial was performed to investigate the impacts of a plyometric training regimen with or without ß-alanine supplementation on anaerobic performance and carnosine levels in male handball players.